RESPONSE OF Cynodon dactylon TO DIFFERENT METHODS OF CONTROL - Sultan, Ahmed M.; Ahmed, Khalid E.; A. , Mahmood N. (Diyala Agricultural Sciences Journal, 2015)
Field experiment was conducted to investigated the efficacy of tillage by chisel (Ch) or disk plow (Di) and herbicides by gramaxon (Gr.) or glyphosate (Gly) on controlling Cynodon dactylon at Hawiy location in the summer growth season 2012 in Nenavia province. The experiment was carried out as factorial experiment , the first factor was methods of weed control (plowing by Di or Ch one time ، Di or Ch two time with duration of 2 and 3 weeks، also Gr at 0.8 L/ha or Gly at 1.92 L/ha for one application ، Gr and Gly sprayed two times with duration 2 and 3 weeks after application. Weedy treatments with three time of taking plant samples were included. The second factor was the time of plant samples .The result showed that percentage of control was super pass in the time of plant samples. The percentage of control was 96.4% , 80.6% , 41.6% ,71.9% for treatments respectively . In general Di plowing was more effect on controlling C.dactylone than Gr. However Ch plowing in the second time of plant samples gave less effect on percentage of weed control (1.13%) with increasing number of plants (15.2 plant/m2),dry weight (317g/m2)and moisture content in plants (473.2g/m2) if it compare with unwedded treatment